Knowledge, perception and belief about HIV/AIDS among health care provider of provincial level hospital outside Kathmandu valley of Bagmati province - Twanabasu, Sajal; Subedi, Bhusan Kumar; Maskey, Sujina; Bhatta, Surenda Prasad; Regmi, Dinesh; Rijal, Ram Chandra (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: Stigmatized health care providers are the strongest hindrances in effectively responding to HIV. This study is conducted to evaluate Human immunodeficiency virus (HIV)/Acquired immunodeficiency virus (AIDS) related knowledge, perception and belief of health care providers working at Dhading hospital, Dhading, Nepal. Method: This is a cross sectional study conducted from 1st to 15th December 2023 among the health professionals of Dhading hospital using a google form questionnaire which consisted of questions related to socio-demographic profile, knowledge regarding testing, transmission along with perception and belief related to HIV/AIDS. Result: Out of 135 respondents, 101 (74.8%) responded among which 59.4% were females and 98% had education of secondary level or above. Majority (>90%) of the participants demonstrated adequate knowledge on questions related to transmission of HIV/AIDS. However, only 75.8% respondents were aware of voluntary counseling and treatment (VCT) with 73.27% still believing HIV/AIDS is a taboo in Nepal. Conclusion: Knowledge, perception and belief of the health care provider is encouraging at Dhading Hospital. Studies like this help to identify gaps and in making appropriate intervention to eliminate stigma and discrimination prevalent among healthcare workers.